MODERN TREATMENT METHODS OF SYSTEMIC SCLERODERMA (World Bulletin of Public Health, 2024)
Systemic scleroderma, a complex autoimmune disease characterized by fibrosis and vasculopathy, poses significant challenges in its management. Significant progress has been made in the development of new therapeutic approaches for systemic scleroderma in the past few decades. This article provides a comprehensive review of current approaches to the treatment of systemic scleroderma, including pharmacological, non-pharmacological, and emerging therapies. The review emphasizes the importance of early diagnosis, multidisciplinary care, and personalized treatment strategies in improving the outcomes of patients with systemic scleroderma
Keywords: Systemic scleroderma; skin and internal organs; immune system; specific pathways